Evidence of new intragenic HBB haplotypes model for the prediction of beta-thalassemia in the Malaysian population - Nur-Aisyah Aziz (Nature Portfolio, 2021)
Abstract This study sought to determine the potential role of HBB haplotypes to predict beta-thalassemia in the Malaysian population. A total of 543 archived samples were selected for this study. Five tagging SNPs in the beta-globin gene (HBB; NG_000007.3) were analyzed for SNP-based and haplotype association using SHEsis online software. Single-SNP-based association analysis showed three SNPs have a statistically significant association with beta-thalassemia. When Bonferroni correction was applied, four SNPs were found statistically significant with beta-thalassemia; IVS2-74T>G (p adj  = 0.047), IVS2-16G>C (p adj  = 0.017), IVS2-666C>T (p adj  = 0.017) and 3’UTR + 314G>A (p adj  = 0.002). However, 3'UTR + 233G>C did not yield a significant association with p adj value = 0.076. Further investigation using combined five SNPs for haplotype association analysis revealed three susceptible haplotypes with significant p values of which, haplotypes 1-2-2-1-1 (p = 6.49 × 10−7, OR = 10.371 [3.345–32.148]), 1-2-1-1-1 (p = 0.009, OR = 1.423 [1.095–1.850] and 1-1-1-1-1 (p = 1.39 × 10−4, OR = 10.221 [2.345–44.555]). Three haplotypes showed protective effect with significant p value of which, 2-2-1-1-1 (p = 0.006, OR = 0.668 [0.500–0.893]), 1-1-2-2-1 (p = 0.013, OR = 0.357 [0.153–0.830]) and 1-1-2-1-1 (p = 0.033, OR = 0.745 [0.567–0.977]). This study has identified the potential use of intragenic polymorphic markers in the HBB gene, which were significantly associated with beta-thalassemia. Combining these five SNPs defined a new haplotype model for beta-thalassemia and further evaluation for predicting severity in beta-thalassemia.